Amelioration of Lead-induced Toxicity in Blood, Liver and Kidney Tissues of Male Wistar Rats by Fermented Ofada Rice - Eferhire Aganbi; Oghenetega Jonathan Avwioroko; Emmanuel Rex Enabulele; Onyeka Joshua Osagu; Chinedu Kennis Uwandu; Assumpta Ike; Aaron Akpede; Prince Eferusuoa (Turkish Journal of Agriculture: Food Science and Technology)
The protective effects of ‘ofada’ rice koji (ORK, fermented ofada rice) and ascorbic acid (AA) against lead (Pb)-induced toxicity in the blood, liver and kidney tissues of male Wistar rats was investigated. The animals were divided into four treatment groups (A – D, n = 5). Groups B, C and D were intoxified by intra-peritoneal injection of 75 mg lead acetate/kg body weight. Groups C and D only had their feed mixed with ORK and AA, respectively. The results showed no significant difference in % packed cell volume (PCV) and Pb concentrations. Feeding with ORK and AA significantly decreased alanine aminotransferase activities (36.50 ± 3.54 and 34.02 ± 0.05 UL-1 respectively) compared to Pb-only treated group (85.50 ± 3.25 UL-1). The ferric reducing antioxidant power (FRAP) for organs increased significantly following intake of feeds mixed with ORK and AA; increases in FRAP was higher for ORK-treated group possibly due to increased total flavonoids concentration following fermentation. Furthermore, Pb-induced high plasma creatinine levels decreased upon treatment with feeds mixed with ORK and ascorbic acid. These findings strongly indicated that feed supplementation with ORK by 45% may be more effective at ameliorating the effects of Pb-induced toxicity in tissues compared to supplementation with AA by 2%.